Managing Dysfunctional uterine bleeding: A Comparative study of Modified Thermal Balloon Ablation vs Thorough Curettage - Mushtaq, Mariam; Ashraf, Afroze; Iqbal, Saima (Biological and Clinical Sciences Research Journal, 2025)
Dysfunctional uterine bleeding (DUB) is a common gynecological problem affecting women in the reproductive and perimenopausal age groups, often resulting in substantial physical, emotional, and social burden. Conventional treatment with thorough curettage has long been practiced in Pakistan; however, modified thermal balloon ablation has emerged as a promising minimally invasive alternative. High-quality comparative local evidence remains limited. Objective: To compare the efficacy and safety of modified thermal balloon ablation versus thorough curettage in achieving cure among women with dysfunctional uterine bleeding. Methods: A randomized controlled trial was conducted at the Gynecology Department of Lady Wallingdon Hospital, Lahore, over 6 months from 3rd July 2024 to 3rd January 2025. Women aged 35–55 years with DUB unresponsive to at least three months of medical therapy were consecutively enrolled and randomly allocated into two equal groups: thorough curettage (Group A) and modified thermal balloon ablation (Group B). Baseline characteristics, intraoperative findings, and follow-up outcomes at 4, 8, and 12 weeks were recorded. Cure was defined as menstrual blood loss less than 80 ml and bleeding duration of fewer than seven days at 12 weeks. Data were analyzed using SPSS 25; t-tests and chi-square tests were applied, with p ≤ 0.05 considered significant. Results: Sixty-two women were included, with comparable baseline demographics in both groups. Modified thermal balloon ablation resulted in significantly lower intraoperative blood loss (28.4 ± 8.7 ml vs 52.6 ± 12.4 ml; p < 0.001) and shorter procedure time (11.1 ± 2.9 minutes vs 17.3 ± 3.8 minutes; p < 0.001) compared to curettage. Bleeding volume and duration decreased significantly more in Group B at all follow-up intervals, most notably at 12 weeks (48.3 ± 16.8 ml vs 91.6 ± 21.1 ml; p < 0.001). Complications were mild in both groups and statistically similar. Cure rates were significantly higher with thermal balloon ablation (90.3%) than with curettage (58.1%) (p = 0.002). Conclusion: Modified thermal balloon ablation demonstrated superior efficacy, achieving higher cure rates with significantly less blood loss and shorter operative time than thorough curettage. The technique offers a safe, effective, and minimally invasive alternative for managing dysfunctional uterine bleeding, especially in resource-constrained settings like Pakistan. It should be considered a preferred treatment option for women with refractory DUB.